Hsa_circ_0004662 Accelerates the Progression of Osteoarthritis via the microRNA-424-5p/VEGFA Axis - Xie, Wei; Jiang, Luoyong; Huang, Xiaoyang; You, Wei; Sun, Wei (Current Molecular Medicine, 2024)
Objective: Circular RNAs (circRNAs) have been extensively implicated in osteoarthritis (OA) progression. Therefore, this study explores the impact of hsa_circ_0004662 on OA progression and the related molecular mechanism.Methods: Human articular chondrocyte injury was induced by IL-1β to construct the OA model in vitro. Hsa_circ_0004662 and microRNA (miR)-424-5p expression in chondrocytes was evaluated with qRT-PCR. Vascular endothelial growth factors A (VEGFA) expression was examined with qRT-PCR and western blot after hsa_circ_0004662 knockdown or miR-424-5p overexpression in chondrocytes. Subsequent to loss- and gain-of-function assays in IL-1β-induced chondrocytes, the proliferation and apoptosis of chondrocytes were assessed with CCK-8 assay and flow cytometry, respectively. The expression of MMP13, Aggrecan, and apoptosis-related proteins Bax and Bcl-2 was measured with western blot. The binding of miR-424-5p to hsa_circ_0004662 and VEGFA was assessed with a dual-luciferase reporter gene assay.Results: Hsa_circ_0004662 was up-regulated, but miR-424-5p was down-regulated in IL-1β-induced chondrocytes. Mechanistically, both hsa_circ_0004662 and VEGFA bound to miR-424-5p, and hsa_circ_0004662 enhanced VEGFA expression by downregulating miR-424-5p. Hsa_circ_0004662 knockdown elevated cell proliferation, decreased apoptosis and MMP13 and Bax expression, and increased Aggrecan and Bcl- 2 expression in IL-1β-induced chondrocytes, which was counteracted by further miR- 424-5p down-regulation or VEGFA overexpression.Conclusion: Hsa_circ_0004662 facilitates OA progression via the miR-424-5p/ VEGFA axis.
Keywords: injury